The roles of the tumor suppressor parafibromin in cancer - Zheng, Hua-chuan; Xue, Hang; Zhang, Cong-yu (Frontiers in Cell and Developmental Biology, 2022)
In this review, we discuss parafibromin protein, which is encoded by CDC73. A mutation in this gene causes hyperparathyroidism-jaw tumor (HPT-JT) syndrome, an autosomal dominant disease. CDC73 is transcriptionally downregulated by the Wilms’ tumor suppressor gene WT1 and translationally targeted by miR-182-3p and miR-155. In the nucleus, parafibromin binds to RNA polymerase II and PAF1 complex for transcription. Parafibromin transcriptionally increases the expression of c-Myc, decreases CPEB1 expression by interacting with H3M4, and reduces cyclin D1 expression by binding to H3K9. The RNF20/RNF40/parafibromin complex induces monoubiquitination of H2B-K120, and SHP2-mediated dephosphorylation of parafibromin promotes the parafibromin/β-catenin interaction and induces the expression of Wnt target genes, which is blocked by PTK6-medidated phosphorylation. Parafibromin physically associates with the CPSF and CstF complexes that are essential for INTS6 mRNA maturation. In the cytosol, parafibromin binds to hSki8 and eEF1Bγ for the destabilization of p53 mRNA, to JAK1/2-STAT1 for STAT1 phosphorylation, and to actinin-2/3 to bundle/cross-link actin filaments. Mice with CDC73 knockout in the parathyroid develop parathyroid and uterine tumors and are used as a model for HPT-JT syndrome. Conditional deletion of CDC73 in mesenchymal progenitors results in embryos with agenesis of the heart and liver while its abrogation in mature osteoblasts and osteocytes increases cortical and trabecular bone. Heterozygous germline mutations in CDC73 are associated with parathyroid carcinogenesis. The rates of CDC73 mutation and parafibromin loss decrease from parathyroid adenoma to atypical adenoma to carcinoma. In addition, down-regulated parafibromin is closely linked to the tumorigenesis, subsequent progression, or poor prognosis of head and neck, gastric, lung, colorectal, and ovarian cancers, and its overexpression might reverse the aggressiveness of these cancer cells. Therefore, parafibromin might be useful as a biological marker of malignancies and a target for their gene therapy.